Improvement of growth and yield of organic broccoli (Brassica oleracea var. Italica) by application of different organic materials combination - Lilik Tri Indriyati; Budi Nugroho (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
Pot experiment was conducted to evaluate the effect of organic materials combination on improvement of growth and yield of organic broccoli. There were 19 treatments in total consisted of four types organic materials that were azolla (A), vermicompost (V), cow dung (S), and chicken manure (F) applied in combination, blank control, and inorganic fertilizer as comparison standard. The experiment results showed that application of organic materials combination significantly increased the growth of plant, diameter head and yield of broccoli compared with untreated soil and inorganic fertilizer treatment. The addition of dolomite into the organic materials combination tended to decrease the growth and yield of broccoli than no addition of dolomite. However, the addition of chicken manure into the combination showed higher growth and yield of broccoli. The best combination of organic materials in raising the growth and yield of broccoli was azolla, and chicken manure (A+F).